CARICOM election observation missions handbook (Caribbean Community Secretariat GeorgetownGY, 2014)
Provides information on election observation in general, background to and terms of reference (TOR) for CARICOM election observation and an aggregation of internationally accepted techniques in election observation that have been developed over the past decade.
Keywords: ELECTIONS